2022
DOI: 10.1002/jsfa.12239
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification, structural characterization, and hepatoprotective effect of the polysaccharide from purple sweet potato

Abstract: BACKGROUND Purple sweet potato Ipomoea batatas (L.) has long been used as a medicine and a food. It contains various bioactive substances such as polysaccharides, anthocyanins, and flavonoids. Purple sweet potato polysaccharides are known to have anti‐oxidant, anti‐tumor, and immunomodulatory functions. Nevertheless, studies on the structural characterization of purple sweet potato polysaccharides and their ability to prevent non‐alcoholic fatty liver disease (NAFLD) have rarely been reported. RESULTS A novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Detailed histological assessments, including Oil Red O, H&E, and Nile red staining, revealed the restorative capability of Jiuzao polysaccharides and VE against ethanol-driven hepatic lipidosis. Li et al [ 15 ] similarly reported that purple sweet potato polysaccharide reduced irregular hepatocyte patterns and excessive lipid vacuoles. Concurrently, we noted decreased activities of SOD and CAT, diminished GSH levels, and increased MDA content within the livers of M group zebrafish larvae, aligning with Lu et al’s research that connects ethanol exposure to hepatic oxidative stress [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed histological assessments, including Oil Red O, H&E, and Nile red staining, revealed the restorative capability of Jiuzao polysaccharides and VE against ethanol-driven hepatic lipidosis. Li et al [ 15 ] similarly reported that purple sweet potato polysaccharide reduced irregular hepatocyte patterns and excessive lipid vacuoles. Concurrently, we noted decreased activities of SOD and CAT, diminished GSH levels, and increased MDA content within the livers of M group zebrafish larvae, aligning with Lu et al’s research that connects ethanol exposure to hepatic oxidative stress [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a hepatoprotective effect has been observed in murine models of liver damage induced by different chemical agents [63]. Administration of sweet potato extracts and/or anthocyanins in murine models decreases levels of liver damage markers such as ALT and AST [66][67][68], as well as serum TG, LDL, and total cholesterol lactate dehydrogenase [69,70]. Its antifibrotic effect was described by Zhang et al, where oral administration decreased hepatic fibrotic tissue in mice intoxicated with carbon tetrachloride [71].…”
Section: Sweet Potatomentioning
confidence: 90%
“…These polysaccharides have been observed to trigger immune responses in macrophages, and promote adaptive immunity in mice by increasing the production of immunoglobulins. A separate investigation demonstrated that the polysaccharide could block the growth of HT-29 cells by inducing apoptosis (Sun et al, 2020;Li et al, 2023;Meng et al, 2023).…”
Section: Sod Activitymentioning
confidence: 99%